Pengembangan Alat Pencetak Pelet Untuk Pakan Ternak Dengan Skala Ekonomis - Farus, Febrianus; Jasron, Jahirwan Ut; Selan, Rima Nindia; Weo, Napsiyana Asti (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
A pellet printing machine is a device specifically designed to produce pig feed using a 1 HP motor with a rotation speed of 1400 RPM. This machine is designed in a vertical form with an internal pressing screw, called a roller. The pressing screw will press the organic mixture towards the perforated printing screen with a hole size of 5 mm to form pellets. This research aims to design a pig feed machine and test its operation over a specific period. The testing of this machine involves collecting experimental data through three repetitions with a mixture weight of 5 kg, consisting of 1 kg of fish meal, 2 kg of organic waste, and 1 kg of rice bran. The collected data includes the capacity of the printed feed over a specific period and the percentage of unprinted material. The results show that the machine can produce pellets with an average effective capacity of 3733.33 g/second and an average yield of 3.33% unprinted material. The production rate achieved is 8.373 kg/hour.